IMPROVING STUDENT WRITING ABILITY IN NARRATIVE TEXT THROUGH THINK TALK WRITE METHOD AT TENTH GRADE OF SMK PGRI 3 CIMAHI - Dina Lisnawati; Diana Elvirasari; Iman Santoso (IKIP Siliwangi, 2019)
The purpose of this research was to find out the improvement of students’ writing abilityin writing narrativetext through think talk write method.The design of this research is point out in the experimental class design. This research will compare the think talk write method and ordinary teaching model. The students’ would learn how to write narrative text. The population of this research was the tenth grade of SMKPGRI 3 cimahi. Therefore, the advantages of this research to invented the new teaching model to the students’, it was good for students’ development in teaching and learning English with a new model of teaching. This study uses quasi experimental design, Data from this study collected through pre-test and post-test, in order to find out some of the results that have increased or decreased, The results show an experimental class with the TTW (Think Talk Write) method. The pre-test results were supported by highest score and the lowest with the highest, pre-test score of 85 while the lowest score was 52, and the post-test score was 52 and the post-test score with the highest score of 93, and the lowest 70. With the pre-test and post-test researchers could compare the assessment